A comparative perspective on minicolumns and inhibitory GABAergic interneurons in the neocortex - Raghanti, Mary Ann; Spocter, Muhammad A.; Butti, Camilla; Hof, Patrick R.; Sherwood, Chet C. (Frontiers in Neuroanatomy, 2010)
Neocortical columns are functional and morphological units whose architecture may have been under selective evolutionary pressure in different mammalian lineages in response to encephalization and specializations of cognitive abilities. Inhibitory interneurons make a substantial contribution to the morphology and distribution of minicolumns within the cortex. In this context, we review differences in minicolumns and GABAergic interneurons among species and discuss possible implications for signaling among and within minicolumns. Furthermore, we discuss how abnormalities of both minicolumn disposition and inhibitory interneurons might be associated with neuropathological processes, such as Alzheimer’s disease, autism, and schizophrenia. Specifically, we will explore the possibility that phylogenetic variability in calcium-binding protein-expressing interneuron subtypes is directly related to differences in minicolumn morphology among species and might contribute to neuropathological susceptibility in humans.